2016
DOI: 10.1017/ice.2016.194
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Risk of Hospital-AcquiredClostridium DifficileInfection With Proton Pump Inhibitor Use: A Meta-Analysis

Abstract: Introduction-Clostridium difficile is the principal infectious cause of antibiotic associated

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
42
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(47 citation statements)
references
References 54 publications
5
42
0
Order By: Relevance
“…In contrast, the odds for an increased occurrence of C difficile infection during PPI therapy are relatively low and PPI‐induced hypochlorhydria was shown not to affect C difficile spore integrity or germination . Instead, it has been hypothesized that PPI‐associated alterations in the gut microbiome may create a niche that facilitates the germination and disease initiation of C difficile infection.…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…In contrast, the odds for an increased occurrence of C difficile infection during PPI therapy are relatively low and PPI‐induced hypochlorhydria was shown not to affect C difficile spore integrity or germination . Instead, it has been hypothesized that PPI‐associated alterations in the gut microbiome may create a niche that facilitates the germination and disease initiation of C difficile infection.…”
Section: Discussionsupporting
confidence: 59%
“…The association of PPI use and Clostridium difficile infection appears evident. [8][9][10][11][12] However, due to limitations in study designs, low odds ratios (OR) and some uncertainties concerning biological plausibility, the available studies cannot ultimately provide sufficient evidence of causality of this association. 13,14 Then again, PPI use and communityacquired bacterial enteric infection show a strong association with a pooled OR of 4.28 (95% CI 3.01-6.08) for any infection, 4.84 (95% CI 2.75-8.54) for Salmonella infection and 5.09 (95% CI 3-8.64) for Campylobacter jejuni infection, as shown in a recent meta-analysis of nine observational studies 15 (Table 1, Figure 2).…”
Section: Ppis and Enteric Infectionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Age-stratified subgroup analysis revealed that there were significant associations of PPI use with increased initial CDI in both adult (OR 2.30, 95% CI 1.89-2.80) and pediatric (OR 3.00, 95% CI 1.44-6.23) patients. As shown in Table 1, several meta-analyses suggested that PPI use significantly increased the risk of primary/recurrent CDI [21,22] and hospital-acquired CDI [23]. Leonard et al [18] reviewed 6 studies including 11,280 patients with Salmonella , Campylobacter , C. difficile , and other enteric infections, and showed that there was an increased risk of PPI use in those with enteric infections (OR 3.33, 95% CI 1.84-6.02).…”
Section: Infectious and Inflammatory Diseases Possibly Associated Witmentioning
confidence: 99%
“…Proton pump inhibitors have been associated with an increased risk of C difficile infection 101112. The effect may also be seen with H2 receptor antagonists…”
Section: Who Is At Risk?mentioning
confidence: 99%